Subalternity with Chinese characteristics - Sun, Wanning (Javnost (Ljubljana), 2012)
Like the indigenous media activists elsewhere, rural migrant individuals in China are now using digital DV camera to produce work to document the lives and work of rural migrants in the Chinese city. In doing so, rural migrant filmmakers provide perspectives which may be alternative to, and critical of, dominant culture. So what kind of political and cultural socialisation is necessary in turning a rural migrant into a cultural activist? What kind of activist imaginary has emerged from this kind of cultural activism? What is the role of NGOs and cultural elites in the development of this cultural phenomenon, and, finally, what challenges and possibility lie ahead for this development? This paper seeks to address these broad questions through two extended case studies of activist initiatives: a rural migrant's journey of becoming an activist filmmaker, and the aspiration and frustrations of a domestic worker film project.
Keywords: Kitajska; ekonomske migracije; migranti; družbena neenakost; socializacija; socialization; množični mediji; mass media; digitalni mediji; dokumenti